2015
DOI: 10.4236/ajps.2015.62043
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Management Strategies to Reduce the Yield Loss Associated with Spring Harvested Corn in Ontario

Abstract: Some growers in northern corn (Zea mays L.) producing regions forgo the typical autumn harvest for various reasons, but not without the risk of significant yield loss. Therefore, strategies are needed for managing the risks to yield when harvesting corn in spring. Field experiments, with various management strategies, were initiated in Ontario, Canada near Belmont and Ridgetown in 2009 and near Belmont, Ridgetown, and Lucan in 2010. Management strategies investigated the use of hybrids with a range in maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In the absence of foliar diseases, strobilurin fungicides may affect physiological processes that may increase corn yields. Increased grain yield may be related to plant health benefits associated with greater water and N use efficiency (Ruske et al, 2003), increased antioxidant activity (Wu and Von Tiedemann, 2002), prolonged canopy greenness, and reduced stalk lodging of corn at harvest (Venancio et al, 2003; Mahoney et al, 2015; Mallowa et al, 2015). Mallowa et al (2015) found that under low disease severity conditions, fungicide application increased yields by 5 to 6% in a recent multistate study.…”
Section: Intensive Agronomic Management Practices Impact Grain Yieldmentioning
confidence: 99%
“…In the absence of foliar diseases, strobilurin fungicides may affect physiological processes that may increase corn yields. Increased grain yield may be related to plant health benefits associated with greater water and N use efficiency (Ruske et al, 2003), increased antioxidant activity (Wu and Von Tiedemann, 2002), prolonged canopy greenness, and reduced stalk lodging of corn at harvest (Venancio et al, 2003; Mahoney et al, 2015; Mallowa et al, 2015). Mallowa et al (2015) found that under low disease severity conditions, fungicide application increased yields by 5 to 6% in a recent multistate study.…”
Section: Intensive Agronomic Management Practices Impact Grain Yieldmentioning
confidence: 99%